2010
DOI: 10.1007/s10806-010-9284-0
|View full text |Cite
|
Sign up to set email alerts
|

Farmer’s Response to Societal Concerns About Farm Animal Welfare: The Case of Mulesing

Abstract: The study explored the motivations behind Australian wool producers' intentions regarding mulesing; a surgical procedure that will be voluntarily phased out after 2010, following retailer boycotts led by People for the Ethical Treatment of Animals. Telephone interviews were conducted with 22 West Australian wool producers and consultants to elicit their behavioral, normative and control beliefs about mulesing and alternative methods of breech strike prevention. Results indicate that approximately half the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Taildocking, on the other hand, was regarded as preventing greater welfare problems from tail-biting; thus it may have been seen as necessary and the ''lesser of two evils'' (cf. Wells et al 2011). In the same vein, one participant supported the once-routine practice of tooth-clipping newborns to prevent painful facial lacerations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taildocking, on the other hand, was regarded as preventing greater welfare problems from tail-biting; thus it may have been seen as necessary and the ''lesser of two evils'' (cf. Wells et al 2011). In the same vein, one participant supported the once-routine practice of tooth-clipping newborns to prevent painful facial lacerations.…”
Section: Discussionmentioning
confidence: 99%
“…Like other food-animal producers (Vanhonacker et al 2008;Phillips et al 2009;Wells et al 2011;Spooner et al 2012), participants generally accepted some invasive management practices as unavoidable. Castration was described as a consumer-driven necessity to avoid boar-tainted meat.…”
Section: Discussionmentioning
confidence: 99%
“…Other conceptual modelling studies have considered the impacts of farmers’ perceptions, attitudes and behaviour on their choice of whether to implement welfare improvements [ 146 ], a matter which has generally been overlooked in other models of animal welfare. Other researchers have applied a conceptual socio-psychological model (the “theory of planned behaviour”) to understand farmers’ decisions, and underlying motivations, to change husbandry practices, such as group housing for pregnant sows [ 147 ], alternatives to mulesing in sheep [ 148 ], and to identify interventions that might encourage farmers to implement such changes [ 147 ].…”
Section: Models In Farm Animal Welfarementioning
confidence: 99%
“…The integration of social scientists into livestock research projects is used at both ends of the research and development pathway, including to explore and address community perceptions of livestock production systems and technologies, as well as farmer decisions to adopt these. Wells et al (2011), for example, explored the motivations behind Australian wool producers' intentions regarding mulesing, and concluded that farmers' intentions to stop or continue mulesing was affected by their perception of social pressure to discontinue mulesing and their ability to implement effective alternatives. In this scenario, the role of the traditional animal scientist addresses only one part of the farmers' decision to change their mulesing practices (i.e.…”
Section: A Broader Role For Animal Sciencementioning
confidence: 99%